Anti-Inflammatory Principles from the Needles of Pinus taiwanensis Hayata and In Silico Studies of Their Potential Anti-Aging Effects - Ping-Chung Kuo; Yue-Chiun Li; Anjar M. Kusuma; Jason T. C. Tzen; Tsong-Long Hwang; Guan-Hong Ye; Mei-Lin Yang; Sheng-Yang Wang (MDPI AG, 2021)
Pinus needle tea are very popular in Eastern countries such as Japan, Russia, Korea, and China. Pine needle tea is claimed to have significant anti-aging effects, but no clear evidence has supported this until now. In the present study, five undescribed compounds (1-5) as well as seventy-two known compounds were purified and characterized from the bioactive fraction of methanol extracts of P. taiwanensis needles. Most of the isolates were examined for their anti-inflammatory bioactivity by cellular neutrophil model and six compounds (45, 47, 48, 49, 50, and 51) exhibited a significant inhibition on superoxide anion generation and elastase release with IC50 values ranging from 3.3 ± 0.9 to 8.3 ± 0.8 μM. These anti-inflammatory ingredients were subjected to docking computing to evaluate their binding affinity on the ghrelin receptor, which played an important role in regulating metabolism, with anti-aging effects. Compounds 49, 50, and 51 formed a stable complex with the ghrelin receptor via hydrogen bonds and different types of interactions. These results suggest the flavonoids are responsible for the potential anti-aging effects of pine needle tea.